Nutritional and health status of adult Syrian refugees in the early years of asylum in Germany: a cross-sectional pilot study - Feras Al Masri; Mattea Müller; Dorothee Straka; Andreas Hahn; Jan Philipp Schuchardt (BMC, 2022)
Abstract Background Migration is usually accompanied by changes in the social, cultural, and religious environment, socioeconomic status, and housing conditions, all of which affect nutritional health. In a cross-sectional study, we assessed the dietary intake as well as nutritional and health situation in a population of Syrian refugees who have resided in Germany for at least six months up to four years since 2015. The primary aim of this pilot study was to evaluate the nutritional and health status in comparison to reference values. Methods Between December 2018 and March 2020, 114 adult Syrian refugees were included in the study. The subjects filled out questionnaires on sociodemographic variables, exercise, and nutrition behavior (three-day nutrition record). After a fasting blood draw, the subjects were examined for anthropometric parameters (height, weight, body mass index, waist circumference, waist-hip ratio, and body composition via a bioelectrical impedance analyzer). Various blood markers including iron status, hematological parameters, Vitamin D status, lipid metabolism, glucose metabolism, and total homocysteine (tHcy) were measured. Results About half of the participants (71 male, 43 female) had lived in Germany for less than three years. Over 60% of men and 30% of women were overweight (BMI 25-30 kg/m2) or obese (BMI > 30 kg/m2), while 79% of men and 74% of women observed an elevated body fat mass. The evaluation of the three-day nutrition records revealed an unfavorable supply situation for numerous critical nutrients. More than half of the women (53.5%) had depleted iron stores (serum ferritin < 15 µg/l). The 25-OH-Vitamin D blood levels showed a high prevalence of Vitamin D insufficiency (25-49.9 nmol/l: 38% of men and 21% of women) and deficiency (< 25 nmol/l: 44% of men and 70% of women). 83% of men and 67% of women showed tHcy levels in plasma > 10 nmol/l. Fasting insulin levels and the HOMA-IR index indicate a risk for insulin resistance. Hyperlipidemia was prevalent, especially in males with 24% showing hypertriglyceridemia (> 150 mg/dl) and LDL-hypercholesterolemia (> 130 mg/dl). Conclusions The nutritional and health status of the cohort of Syrian refugees in Germany examined in this study is unsatisfactory, and many of the investigated refugees are at risk for developing cardiovascular disease and type 2 diabetes mellitus. Further studies are required to investigate the nutritional and health situation of refugees. This is obligatory to find ways to avoid malnutrition with all its associated health, sociodemographic, and economic consequences.